Expression of tissue factor in rabbit pulmonary artery in an acute pulmonary embolism model - Zhang, Jing-xia (Second Affiliated Hospital of Zhejiang University School of Medicine, 2014)
BACKGROUND: Tissue factor (TF) is the initiation factor of the extrinsic coagulation pathway, and plays a critical role in the process of thrombosis. This study aimed to investigate the expression of TF and to explore their clinical effect on the pulmonary artery after acute pulmonary thromboembolism. METHODS: Thirty-four Japanese white rabbits (Level II animals) supplied by Tianjin Medical University were randomly assigned into: group A, specimens of the pulmonary artery taken 3 hours after pulmonary embolism (n=8); group B, specimens of the pulmonary artery taken 8 hours after pulmonary embolism (n=8); group C, specimens of the pulmonary artery taken 24 hours after pulmonary embolism (n=8); and control group, pseudo-operations performed without injection of autologous blood clots (n=10). The animal model of pulmonary thrombo-embolism was established by injection of autologous blood clots into the jugular vein through a 5F catheter, and was confirmed by digital subtraction angiography. The mRNA expression of TF in different parts of the pulmonary artery was accessed by RT-PCR. The q test was used if there was a significant difference in a given continuous variable among the three groups assessed by ANOVA. The experiment equipment was supplied by the State Key Laboratory of Experimental Hematology, Institute of Hematology and Blood Diseases Hospital, the Chinese Academy of Medical Sciences and Peking Union Medical College. RESULTS: The TF expression in the specimen adjacent to emboli was stable at 3, 8 or 24 hours after embolism. The mRNA expression of TF at 3 and 8 hours after embolism was lower in the specimens taken from the distal end of the morbid pulmonary artery than those adjacent to emboli. While at 24 hours after embolism, there were similar mRNA levels in specimens either adjacent or distal to emboli. CONCLUSION: The high level of TF expression in pulmonary artery tissue adjacent to emboli could lead to locally increased coagulation activity, indicating the necessity of initiating anti- coagulation treatment as soon as possible after acute pulmonary embolism.